Pengaruh Muhammad Abduh Di Kepulauan Melayu-Indonesia - ahmad nabil amir (Jurnal Al-Hikmah: Jurnal Dakwah, 2021)
Muhammad Abduh had a remarkably profound and lasting impact in South East Asia. His works and ideas were highly influential in the region with strong repercussion in its political and social landscape. He had strongly impacted the movements of Muhammadiyah, al-Irsyad and Persatuan Islam (Persis). His Tafsir al-Manar had broke the ground with rational outlook that influence major works of tafsir such as Tafsir al-Azhar, Tafsir al-Quranul Karim, Tafsir al-Qur’an al-Madjied (Tafsir al-Nur), Tafsir al-Qur’an al-Hakim, Tafsir al-Misbah and Tafsir al-Furqan. The Majallah al-Manar initiated by Muhammad Abduh had significantly inspired many reform oriented works and periodicals such as journal al-Imam, al-Munir, al-Ikhwan, Saudara, al-Dhakhirah al-Islamiyah and Seruan Azhar. Thus this paper attempts to survey Abduh’s extensive influence and its impact on Islamic reform (tajdid) in the Malay Archipelago.